MEDIATORS OF RACIAL AND ETHNIC DISPARITIES IN HYPERTENSIVE DISORDERS OF PREGNANCY AND TARGETED INTERVENTIONS - Xudayberdiyeva Ruqiya; Sayfullayeva Hilola; Axtamova Nilufar Akbarjanovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Racial and ethnic disparities in hypertensive disorders of pregnancy (HDP) extend beyond direct demographic factors, involving mediating elements such as allostatic load, environmental chemical exposures, nativity status, and provider bias. This thesis explores these mediators' roles in exacerbating HDP risks, particularly among non-Hispanic Black and Hispanic populations compared to non-Hispanic White groups. Utilizing recent cohort and retrospective data, it highlights how chronic stress embodiment (allostatic load), differential chemical exposures, immigration-related protections, and biased clinical responses contribute to unequal outcomes. Interventions proposed include bias mitigation training, universal escalation protocols, community-engaged research on cumulative exposures, and policies addressing structural inequities. A synthesis of 2024-2025 studies emphasizes the urgency of integrating these mediators into clinical and public health frameworks to reduce HDP morbidity and mortality gaps.